Exploring the influential factors of continuance intention to use mobile Apps - Tam, Carlos (2020)
Tam, C., Santos, D., & Oliveira, T. (2018). Exploring the influential factors of continuance intention to use mobile Apps: extending the expectation confirmation model. Information Systems Frontiers, 1-15. https://doi.org/10.1007/s10796-018-9864-5 ---%ABS3%